Effects of cardioactive drugs on human induced pluripotent stem cell derived long QT syndrome cardiomyocytes - Kuusela, Jukka (Springerplus, 2016)
Human induced pluripotent stem cells (hiPSC) have enabled a major step forward in pathophysiologic studies of inherited diseases and may also prove to be valuable in in vitro drug testing. Long QT syndrome (LQTS), characterized by prolonged cardiac repolarization and risk of sudden death, may be inherited or result from adverse drug effects. Using a microelectrode array platform, we investigated the effects of six different drugs on the electrophysiological characteristics of human embryonic stem cell-derived cardiomyocytes as well as hiPSC-derived cardiomyocytes from control subjects and from patients with type 1 (LQT1) and type 2 (LQT2) of LQTS. At baseline the repolarization time was significantly longer in LQTS cells compared to controls. Isoprenaline increased the beating rate of all cell lines by 10–73 % but did not show any arrhythmic effects in any cell type. Different QT-interval prolonging drugs caused prolongation of cardiac repolarization by 3–13 % (cisapride), 10–20 % (erythromycin), 8–23 % (sotalol), 16–42 % (quinidine) and 12–27 % (E-4031), but we did not find any systematic differences in sensitivity between the control, LQT1 and LQT2 cell lines. Sotalol, quinidine and E-4031 also caused arrhythmic beats and beating arrests in some cases. In summary, the drug effects on these patient-specific cardiomyocytes appear to recapitulate clinical observations and provide further evidence that these cells can be applied for in vitro drug testing to probe their vulnerability to arrhythmia. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s40064-016-1889-y) contains supplementary material, which is available to authorized users.